Exploring Inclusivity: Challenges, Strategies, and Impact - Meghna Jain; Deepti Pande Rana (International Journal of Rural and Regional Development, 2024)
Inclusivity is a cornerstone which aims to create environments, products and systems that meet the diverse needs and abilities of all people. This research paper provides a comprehensive study of inclusivity and sheds light on its role in building a just and accessible world. It continues to trace the historical development of universal design, revealing key milestones and their impact on the pursuit of inclusivity. In addition, the article examines the current landscape of inclusivity in various fields such as architecture, product design, digital technology, transportation and more, revealing both important achievements and ongoing challenges. A significant part of this research is dedicated to examining the specific effects of inclusivity on people with different needs, emphasizing its potential to increase social well-being, reduce inequalities and promote social integration. In addition, the economic and social implications of incorporating participatory practices into universal design are explored, highlighting wider benefits for communities and economies. In addition, the article examines global standards and legal frameworks related to universal design and inclusivity, providing an overview of the collective efforts to promote the principles of inclusive and accessible design at the international level. Presenting various case studies and best practices from different regions and industries, successful examples of integrating inclusion into universal design are presented. Finally, the article outlines an agenda for future research and development and highlights the importance of continued collaboration between designers, policy makers, researchers and individuals with disabilities to promote inclusivity in universal design. It concludes with a powerful call to action, encouraging stakeholders to prioritize inclusivity as a key pillar of universal design, promoting a society that embraces inclusivity, accessibility and equality for all. This research paper is a comprehensive resource for researchers, practitioners and policy makers interested in understanding and advocating universal design, ultimately contributing to a more inclusive and just world.
Keywords: Abilities; Accessible world; Equality; Inclusive design; Individuals with disabilities